Conditions to Prolonged Release of Microencapsulated Carvacrol on Alginate Films as Affected by Emulsifier Type and PH - Silvia Matiacevich; Natalia Riquelme; María Lidia Herrera (International Journal of Polymer Science)
Alginate from algal biomass is used as edible film and the incorporation of antimicrobial agents improves its performance to increase the shelf-life of fresh foods. However, environmental conditions and intrinsic properties of films influence their release. The aim of this study was to investigate the effect of the concentration and type of encapsulating agent and pH of emulsions on the physical and antimicrobial properties of alginate-carvacrol films. Films containing alginate, carvacrol as antimicrobial agent, and Tween 20 or trehalose (0.25 and 0.75% w/w) as encapsulating agents were obtained from suspensions at pH 4 and pH 8. Physical characterization of emulsions and films and antimicrobial properties (E. coli and B. cinerea) was evaluated. Results showed that droplets size depended on trehalose concentration, but emulsion stability depended on pH and type of encapsulating agent, being more stable samples with trehalose at pH 4. Although films with Tween 20 presented the highest opacity, they showed the best antimicrobial properties at initial time; however, during storage time, they lost their activity before samples with trehalose and relative humidity (RH) was the principal factor to influence their release. Therefore, sample formulated with 0.25% trehalose at pH 4 and stored at 75% RH had the best potential as edible film for fresh fruits.